New donors, loyal donors, and regular donors: Which motivations sustain blood donation?. Issue 3 (June 2015) - Guiddi, Paolo; Alfieri, Sara; Marta, Elena; Saturni, Vincenzo
Abstract: Background: The present contribution aims to investigate the motivations underlying blood donation and to probe how these differ on the basis of number of donations and donors' gender. Materials and methods: A total of 237 Italian donors (64.6% male) were administered a self-report questionnaire containing socio-demographic variables and Omoto and Snyder's Motivations for Volunteerism Scale adapted to blood donation. Results and discussion: The results reveal: (a) significant differences between new donors (1–4 donations) and loyal donors (5–15 donations) as well as between new donors and regular donors (more than 16 donations) emerge with respect to social motivations and ego-protection, which increase proportionately to number of donations; (b) gender differences characterize all the motivations except those related to values; (c) value motivations do not vary either with respect to number of donations or to gender.